Relative resistance index (RRI) – a scoring system for antibiotic resistance in Pseudomonas aeruginosa. Issue 4 (2nd October 2017) - Ewing, J; McCaughan, J; Moore, J; Fairley, D; Sutherland, B; Reid, A; Downey, D
Abstract: Background: There is a need to measure antibiotic resistance of Pseudomonas aeruginosa (PA) in cystic fibrosis (CF), either qualitatively or quantitatively, to inform patient management. The aim of this study was to develop a simple method by which resistance can be quantified by calculating a relative resistance index (RRI), and to assess correlation of RRIs with clinical variables. Methods: In our model, RRIs were calculated based on resistance to aztreonam, ceftazidime, ciprofloxacin, colistin, meropenem, tazocin, temicillin and tobramycin. Eighty-five adults with CF and chronic PA colonisation were identified. For each, all PA cultures were allocated a score of 0 for susceptible, 0.5 for intermediate resistance or 1 for resistance for each antibiotic listed above, and the RRI calculated by dividing the sum of these by the number of antibiotics, giving a maximum score of 1. The mean RRIs for all cultures were correlated with key clinical variables monitored in CF patients (including age, FEV1, IV antibiotic days and BMI). Results: RRIs for non-mucoid PA exhibited moderate positive correlation with total number of IV days ( r = 0.405; p < 0.001) and moderate negative correlation with FEV1 % predicted ( r = −0.437; p < 0.001). RRIs were not significantly correlated with duration of colonisation, typing (clonal vs other strain) or BMI. Median RRIs were significantly higher for females (0.26, IQR 0.13–0.54) than males (0.18, IQR 0.07–0.37) for non-mucoid PA only ( p = 0.03). Conclusions: RRI is an easily calculated measure that correlates with other clinical variables in CF patients and enables quantitative monitoring of resistance.